Nyeri Sebelum Kemoterapi sebagai Prediktor Rendahnya Kualitas Hidup Penderita Leukemia Limfoblastik Akut (LLA) Anak-Anak - DANUAJI, RIVAN; MULATSIH, SRI; SUTARNI, SRI (Indonesian Journal of Cancer, 2010)
Chemotherapy and stem cell transplantation are the main therapy in childhood leukemia. Pain is one of symptom that may occur in acute lymphoblastic leukemia (ALL) and may influence quality of life (QOL). The aim of this study is to determine correlation between pain before chemotherapy and the QOL of children with ALL. A cohort retrospective study was conducted. Quality of life was measured by PedsQLTM 3,0 version. Univariate analysis showed 7 factors as predictor of QOL. There were age, fatherâs and motherâs education, family income, riskâs group, pain after and before chemotherapy. Multivariate analysis showed family income (RR: 1,61; 95% CI: 1.50 â 17.29) and pain after chemotherapy (RR: 3.24, 95% CI: 1.36 â 7.68) were significantly influenced ALL childhoodâs QOL. Pain before chemotherapy could be used as a predictor of ALL childhoodâs QOL. Family income and pain after chemotherapy was independent predictor.